Immigrant generation, acculturation, and mental health literacy among former Soviet Union immigrants in Israel. (May 2023) - Knaifel, Evgeny; Youngmann, Rafael; Neter, Efrat
Background: Research on Mental Health Literacy (MHL) has been growing in different geographical and cultural contexts. However, little is known about the relationship between immigrant generations, acculturation, stigma, and MHL among immigrant populations. Aims: This study aims to examine differences in MHL among immigrant generations (first, 1.5, and second) from the former Soviet Union (FSU) in Israel and to assess whether differences are accounted for by immigration generation or acculturation. Method: MHL was assessed among 420 participants using a cross-sectional survey adapted from the Australian National Survey. Associations of immigrant generation, socio-demographic characteristics, and acculturation with MHL indices were examined using bivariate and multivariable analyses. Results: First generation immigrants reported poorer identification of mental disorders and higher personal stigma than both 1.5- and second-generation immigrants. Acculturation was positively associated with identification of mental disorders and negatively associated with personal stigma across all immigrants' generations. When all variables were entered into a multivariate model predicting MHL indices, acculturation and gender were associated with personal stigma and only acculturation was associated with better identification of mental disorders. Conclusion: Differences in MHL among FSU immigrants in Israel are mainly explained by acculturation rather than by immigrant generation. Implications for policy makers and mental health professionals working with FSU immigrants are discussed.